DEVELOPMENT OF AL-MASTER MODEL-BASED STUDENT WORKSHEET TO IMPROVE CRITICAL THINKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Siti Lestari; Caswita Caswita; Sri Hastuti (Aksioma: Jurnal Program Studi Pendidikan Matematika)
This study aims to develop and review the effectiveness of learning student worksheet based on the AL-MASTER model to improve students' critical thinking skills. The research was conducted at SMP Negeri 1 Purbolinggo. This type of research is research and development or Research and Development (R&D). The research and development process includes four stages: defining, planning, developing, and disseminating. The analysis included (1) data analysis of questionnaire validation of teaching materials and respondents and (2) analysis of critical thinking ability test data. The results of the analysis show that after using the AL-MASTER Model-based LKPD, it can be concluded that (1) The average results of expert assessment of the feasibility level of product development are in the feasible category, (2) The results of product trials and reviewing students' critical thinking skills show an increase in the Pre-Test average and the Post-Test average in class VIII.1 and the results of the N-gain percentage for that class were 68.74% with quite effective criteria, (3) Learning showed that time efficiency in class VIII.1 was quite efficient and the percentage of completeness in the experimental class was 74.17% or 26 students complete while the percentage of completeness, and (4) the response of teachers and students in the category was exciting.